Intelligent sliding mode control using natural logarithm sliding surface - Ridhuan Siradj , Fadly Jashi Darsivan (2010)
In automotive, engine mount is a component used to support the car engine on the chassis and at the same time isolates engine vibration. Ideally engine mount system should isolate engine vibration caused by engine disturbance force in engine speed range and prevent engine bounce from shock excitation. Nowadays, active engine mounting system has been considered as the next generation of engine mounts.